Jejak sejarah dan tradisi Sendang Made: Refleksi identitas nasional berbasis kearifan lokal - Hadiningsih, Dian Rosita (Maliki Interdisciplinary Journal, 2026)
This study aims to explore the role of local wisdom in strengthening national identity through a case study of the Sendang Made site in Jombang Regency. As a multicultural nation, Indonesia faces significant challenges in maintaining its identity amidst globalization and digital transformation. Using a qualitative-descriptive approach and literature study, this research analyzes the historical relationship between Sendang Made and King Airlangga’s exile, as well as the philosophical meaning of annual rituals including Nguras Sendang, Sedekahbumi, and Wisuda Sinden. The results show that the sacredness of Sendang Made is not merely a myth but has a historical foundation recorded in the collective memory of the community and supported by the Pucangan Inscription. The enduring traditions at this site serve as evidence of the resilience of mutual cooperation (gotong-royong) and spirituality, which form the foundation of national identity. This study concludes that strengthening cultural literacy based on local wisdom is a crucial strategy to protect the national character from external influences that may erode patriotism.